Association between mistreatment of women during childbirth and symptoms suggestive of postpartum depression - Janini Cristina Paiz; Stela Maris de Jezus Castro; Elsa Regina Justo Giugliani; Sarah Maria dos Santos Ahne; Camila Bonalume Dall' Aqua; Camila Giugliani (BMC, 2022)
Abstract Background Postpartum depression is a common condition in the pregnancy and postpartum cycle. The development of this condition is multifactorial and can be influenced by previous traumas. This study sought to verify whether there is an association between having been exposed to mistreatment during childbirth and presenting symptoms suggestive of postpartum depression. Methods This is a cross-sectional study, with the inclusion of 287 women without complications in childbirth, randomly selected from two maternity hospitals of Porto Alegre, southern Brazil, in 2016. Four weeks after delivery, the postpartum women answered a face-to-face interview about socioeconomic aspects, obstetric history, health history, and childbirth experience (practices and interventions applied) and completed the Edinburgh Postnatal Depression Scale (EPDS). From the perception of women regarding the practices performed in the context of childbirth care, a composite variable was created, using item response theory, to measure the level of mistreatment during childbirth. The items that made up this variable were: absence of a companion during delivery, feeling insecure and not welcome, lack of privacy, lack of skin-to-skin contact after delivery, not having understood the information shared with them, and not having felt comfortable to ask questions and make decisions about their care. To define symptoms suggestive of postpartum depression, reflecting on increased probability of this condition, the EPDS score was set at ≥ 8. Poisson Regression with robust variance estimation was used for modeling. Results Women who experienced mistreatment during childbirth had a higher prevalence of symptoms suggestive of postpartum depression (PR 1.55 95% CI 1.07-2.25), as well as those with a history of mental health problems (PR 1.69 95% CI 1.16-2.47), while higher socioeconomic status (A and B) had an inverse association (PR 0.53 95% CI 0.33-0.83). Conclusions Symptoms suggestive of postpartum depression seem to be more prevalent in women who have suffered mistreatment during childbirth, of low socioeconomic status, and with a history of mental health problems. Thus, qualifying care for women during pregnancy, childbirth and postpartum and reducing social inequalities are challenges to be faced in order to eliminate mistreatment during childbirth and reduce the occurrence of postpartum depression.